THE CHANGES OF THE ELECTROPHYSIOLOGICAL PROPERTIES OF NEURONS BY THE ACTION OF SEVOFLURANE AND THEIR ROLE IN THE MECHANISMS OF PRECONDITIONING AND CYTOPROTECTION - A. I. Vislobokov; Yu. S. Polushin; A. Yu. Polushin; V. V. Alferova (Вестник анестезиологии и реаниматологии)
The changes of the intracellular potentials by the action of sevoflurane were studied for the diagnostic intact neurons of the isolated cerebrospinal axis of the Planorbarius corneus using intracellular electrodes. There observed a two-phase reaction of the neurons de- and hyperpolarization. The sevoflurane concentration of 2 mM depolarized the neurons (to 5 mV), the depolarization was interchanged with the mild hyperpolarization (at 2-5 mV). The impulse activity rate (IA) increased under  depolarization, while decreased under  hyperpolarization, the parameters of the action potentials (AP) changed slightly. The inversive hyperpolarization occurred for 5-10 minutes upon the anesthetic elimination. There occurred the short-term and inversive depolarization of the neurons at the sevoflurane concentration of 5 mM to 9,4 ± 2,2% of the reference, while the IA rate increased, the amplitude of the action potentials decreased with their duration increase, and sometimes the AP generation was completely abrogated. On action of sevoflurane concentration of 5 mM there developed the inversive hyperpolarization of the neurons to 18,1 ± 16,9% of the reference, that lasted 15-20 minutes thereafter. The  repeated neuron exposure with  the  same anesthetic is  always reproduced followed by  the  florid hyperpolarization. The  modulation of  the  electrical activity with  sevoflurane (the  hyperpolarization of  the  neurons and the decrease/termination of AP generation that evidenced the "improvement" of their functional status) may be the basis for the preconditioning, neuro- and cardioprotection.